1961
DOI: 10.1111/j.1365-2494.1961.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

The Production and Utilization of Winter Grass at Various Centres in England and Wales, 1954–60

Abstract: The effects of management on the production of winter grass wen studied of 47 site England and Wales from 1954 to 1958. Cocksfoot swards provided better grazing during December and January than perennial ryegrass. The best treatment for winter‐grass production from cockfoot swards was to rest from mid‐August, giving un application of 52 lb of nitrogen per acre at this time. Perennial ryegrass produced relatively high yields if rested from early September, but the herbage should be grazed before the end of Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

1961
1961
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…The overall mean response to N was 12·0 kg DM kg −1 N (range 1·5–29·7 kg DM kg −1 N) which not only falls within the range found in cutting experiments during the normal growing season (Bartholomew and Chestnutt, 1977) but also compares with that found by Baker et al . (1961a), Wilkinson (1985) and Skinner and Allen (1991) for N applied specifically to produce herbage for late autumn/winter utilization.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The overall mean response to N was 12·0 kg DM kg −1 N (range 1·5–29·7 kg DM kg −1 N) which not only falls within the range found in cutting experiments during the normal growing season (Bartholomew and Chestnutt, 1977) but also compares with that found by Baker et al . (1961a), Wilkinson (1985) and Skinner and Allen (1991) for N applied specifically to produce herbage for late autumn/winter utilization.…”
Section: Discussionsupporting
confidence: 86%
“…Herbage mass at each of the harvest dates was as high as, or higher than, those obtained in other experiments where the objective was to produce herbage for the late autumn/winter period (Baker et al ., 1961a; Castle and Watson, 1961; Wilkinson, 1985; Skinner and Allen, 1991). Compared with the zero N treatment, progressively increasing the rate of N application increased the herbage mass at each harvest.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…There are no research studies concerning the quality and production capacity of grass stands in the autumn and winter. Many authors have studied the quality and yield of herbage in the autumn and winter; they also investigated the possibilities of a prolongation of the grazing season but mostly under conditions of Atlantic climate and overseas (Baker et al, 1961;Frame, 1970;Opitz von Boberfeld and Wolf, 2002). The territory of the Czech Republic is infl uenced by Atlantic climate only during the summer months while in winter the infl ux of cold air from Siberia predominates.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al (2) and Gardner (9) noted considerably more rotting in broadcast swards; and Corbett (6) suggested that less dense swards would be more desirable because they would be less subject to rotting. Stock appear to waste less herbage when grazing a row crop (11).…”
Section: Introductionmentioning
confidence: 96%